2019
DOI: 10.1080/13691058.2019.1581897
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision-making around anal cancer screening among black bisexual and gay men in the USA

Abstract: Shared decision making is a strategy to achieve health equity by strengthening patient-provider relationships and improve health outcomes. There is a paucity of research examining these factors among patients who identify as sexual or gender minorities and racial/ethnic minorities. Through intrapersonal, interpersonal and societal lenses, this project evaluates the relationship between intersectionality and shared decision making around anal cancer screening in Black gay and bisexual men, given their dispropor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“… 12 16 The project captured the stories, views, preferences, and recommendations of these patients through audiotaped interviews and focus groups. 7 , 17 , 18 After analyzing these data, our team invited five participants to be reinterviewed and share their stories through video. We created five 10- to 15-minute videos to capture a range of lived experiences and stories navigating health care, including a Latina lesbian gender nonconforming individual with a history of obesity/body image issues, an older African American gay man, an African American transfemme individual with chronic health conditions, a Latina transsexual woman, and an Asian American transmasculine individual who was a survivor of intimate partner violence (all self-defined identities).…”
Section: Methodsmentioning
confidence: 99%
“… 12 16 The project captured the stories, views, preferences, and recommendations of these patients through audiotaped interviews and focus groups. 7 , 17 , 18 After analyzing these data, our team invited five participants to be reinterviewed and share their stories through video. We created five 10- to 15-minute videos to capture a range of lived experiences and stories navigating health care, including a Latina lesbian gender nonconforming individual with a history of obesity/body image issues, an older African American gay man, an African American transfemme individual with chronic health conditions, a Latina transsexual woman, and an Asian American transmasculine individual who was a survivor of intimate partner violence (all self-defined identities).…”
Section: Methodsmentioning
confidence: 99%
“…This model was developed to provide an understanding of SDM with Black lesbian, gay, bisexual, transgender and queer persons (Figure 1) (Peek et al 2016). It has been previously applied to understanding the relationship between intersectionality and SDM for anal cancer screening among Black gay and bisexual men (Acree et al 2019).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…In the Peek Model, the patient, the health provider and their relationship are viewed in multiple ways (Acree et al 2019;Peek et al 2016). The individual level, or the level of self-perception, describes how both the patient and provider view themselves in the context of their identity (e.g.…”
Section: Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions had significant influences on HIV and other sexually transmitted infections (STI) screening behaviors among MSM, and they are modifiable through interventions [ 30 , 31 , 32 ]. Qualitative studies suggested that perceived stigma originated from service providers related to their sexual orientation or HIV sero-status; barriers for MSM to receive HPV tests included embarrassment and discomfort, fear of positive results, and perceived low risk of anal cancers [ 26 , 33 , 34 ]. These factors were considered by this study.…”
Section: Introductionmentioning
confidence: 99%